Real-Time Continuous Glucose Monitoring and Diabetes Treatment - Sinclair, Heather Q. (MD Conference Express, 2010)
Real-time continuous glucose monitoring (RT-CGM) provides valuable information about glucose trends and patterns in diabetic patients. Recent trial data may provide evidence that supports the widespread use of RT-CGM in patients with type 1 diabetes mellitus. This article discusses recent landmark CGM studies and the clinical implications of these findings.